Determinants of quality romantic relationship among emerging adults in tertiary institutions in Oyo state, Nigeria (2015)
Romantic relationships undoubtedly play a major role in the lives of most young adults since it is the building blocks for a healthy adult marriage. However, attachment style formed in early life through interaction with caregivers and significant others and the individual’s personality composition provide a spring board for quality romantic relationship in readiness for marriage. The present study using descriptive survey research design, investigated the predictive influence of personality traits, attachment styles, age and gender on quality romantic relationship among emerging adults in tertiary institutions in Oyo state. The sample comprised male and female young adults (N=450) aged between 18- 25years old who responded to three standardized self report questionnaires. Three research questions were raised and answered in the -study. Results indicated that there was significant correlations among the independent variables with correlation coefficients ranging from r=.286 to r=.861 with quality romantic relationship. Multivariates regression analyses indicated that the contribution of the independent variable was significant [F (9,44;) = 2.37; p<.0.05] which jointly accounted for about 92.2% variation in the prediction of quality romantic relationship. Conscientiousness made the most significant contribution (β= 1.096; t= 31.483; p<0.05) to the prediction while neuroticism (β= .003; t=.128; p>0.05) and gender (β= .004; t= .007; p>0.05) had insignificant relative contribution. The study provides empirical evidence to suggest that psychological factors, like age and gender have a role to play in quality romantic relationship among emerging adults